2016
DOI: 10.20517/2394-4722.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

The role of the PI3K/AKT/mTOR pathway in brain tumor metastasis

Abstract: The PI3K/AKT/mTOR (PAM) pathway is involved in a variety of cellular functions and often contributes to oncogenesis and cancer progression. It has been recognized that this pathway is frequently activated in the most common central nervous system cancers of adults and children, malignant gliomas and medulloblastomas (MB). In these tumors, the PAM network controls key functions necessary for cell invasion and metastasis, such as cell motility. This review summarizes the current knowledge about the role of PAM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 126 publications
(142 reference statements)
1
30
0
Order By: Relevance
“…Our results also showed that the enhanced expression of LOX downstream of the PI3K-Akt-HIF-1α signaling was necessary for migration and invasion of cancer cells carrying the activated ras genes. It is well recognized that the PI3K-Akt signaling plays critical roles in metastasis of cancer cells by promoting cellular events such as invasion, migration and epithelial-mesenchymal transition (EMT) via activation of the transcription factors, Twist and Snail, and inhibition of GSK-3β [30][31][32]. Our results implied that LOX also plays a critical role in metastasis working in parallel with these known PI3K-Akt target proteins.…”
Section: Discussionsupporting
confidence: 55%
“…Our results also showed that the enhanced expression of LOX downstream of the PI3K-Akt-HIF-1α signaling was necessary for migration and invasion of cancer cells carrying the activated ras genes. It is well recognized that the PI3K-Akt signaling plays critical roles in metastasis of cancer cells by promoting cellular events such as invasion, migration and epithelial-mesenchymal transition (EMT) via activation of the transcription factors, Twist and Snail, and inhibition of GSK-3β [30][31][32]. Our results implied that LOX also plays a critical role in metastasis working in parallel with these known PI3K-Akt target proteins.…”
Section: Discussionsupporting
confidence: 55%
“…Although the loss of CDKN2A/2B genes can be detected in samples with tumor contents <35% (a threshold set at the fold change cutoff of 0.65 for copy number loss), there is the possibility that no detection in primary NSCLC was due to the lower tumor content in comparison with BMs in 2 cases (P4 and Cancer October 15, 2019 P25). 30 Therefore, components of the PI3K signaling pathway are considered potential drug targets to inhibit the often fatal events of metastasis and cell invasion. Previous studies have reported that the amplification of CDK genes is important for functional inactivation of CDKs/RB regulatory complexes in aggressive cancers of the central nervous system, including medulloblastomas and glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…28 It has also been reported that the PI3K pathway controls key functions necessary for cell invasion and metastasis, including cell motility, 29 and is frequently activated in the most common central nervous system cancers of adults and children, such as malignant gliomas and medulloblastomas. 30 Therefore, components of the PI3K signaling pathway are considered potential drug targets to inhibit the often fatal events of metastasis and cell invasion. However, the performance of kinase inhibitors in clinical trials has been poor thus far because of small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Whether Snail is also involved needs to be explored in future research. Increasing evidence indicates that the PLC, ERK, p38, and β‐catenin signaling pathways are mediated in melatonin‐associated control of cellular effects . Stimulation of PLC, ERK, p38, and β‐catenin activators confirm that these signaling pathways regulate melatonin‐induced reductions in lung cancer stemness.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, outcomes of the sphere formation assay showed that melatonin inhibits lung cancer stemness. Increasing reports suggest that the phospholipase C (PLC), ERK, p38, and Wnt/β‐catenin signaling pathways mediate melatonin‐regulated cell functions . In addition, Twist has been documented as being a critical epithelial‐mesenchymal transition (EMT) and cancer stemness regulator .…”
Section: Introductionmentioning
confidence: 99%